Plano de gerenciamento sustentável dos resíduos de construção civil. O caso de Rio Claro (SP) - Suzuki, Felipe Kazuo Shimizu [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The current problematic of the construction and demolition (C&D) waste faced for the Brazilian cities, is one of the main degradation factors of the environment, over all about the promise of the urban ambient quality. This scenery must mainly to the unsustainable management adopted by the great majority of the Brazilian cities. Therefore, this work aims at to offer subsidies for medium cities, having as study object the city of Rio Claro-SP, (Brazil), in the elaboration of plans and integrated programs of sustainable management of the construction and demolition waste, in accordance with CONAMA Resolution nº 307/2002, that’s set up a sustainable management system of C&D waste. In this direction, the diagnosis of the management was elaborated for the city of Rio Claro, (generation, collects, transport and disposal) and the public administration of the construction and demolition waste, as well as of the study of the related aspects with C&D waste recycling plant. Later, was suggested a plan of improvements for the public manager of C&D waste: areas of temporary disposal to facility the appropriating destination, appropriated areas of final disposal, incentives to the recycling of C&D waste, new legislations, education and orientation programs and adequacy the agents of C&D waste management (generating, transporting, addressee and public manager), directing for an environmental, economic and social sustainability.

A atual problemática dos resíduos de construção civil (RCC), enfrentada pelos municípios brasileiros é um dos principais fatores de degradação do meio ambiente, sobretudo do comprometimento da qualidade ambiental urbana. Tal quadro deve-se principalmente ao gerenciamento insustentável adotado pela grande maioria dos municípios brasileiros. Assim, este trabalho visa oferecer subsídios para municípios de médio porte, tendo como objeto de estudo o município de Rio Claro-SP, na elaboração de planos e programas integrados de gerenciamento sustentável dos resíduos de construção civil, de acordo com a resolução CONAMA nº 307/2002. Nesse sentido, elaborou-se para o município de Rio Claro (SP) o diagnóstico do gerenciamento (geração, coleta, transporte e destinação) e da gestão pública dos resíduos de construção civil, bem como do estudo dos aspectos relacionados à usina de reciclagem de RCC. Posteriormente, propôs-se um plano de melhorias principalmente para a gestão pública (responsável pelo gerenciamento dos RCC), sugerindo: a criação de Ecopontos (áreas para facilitação da destinação adequada dos RCC), áreas para aterro de resíduos da construção civil (disposição final), incentivos à reciclagem de RCC, criação de legislações específicas, programas de educação ambiental e adequação dos agentes atuantes do gerenciamento dos RCC (gerador, transportador, destinatário e administração pública), visando sua sustentabilidade ambiental e sócio-econômica.
Keywords: Resíduos; Resíduos sólidos; Resíduos de construção civil; Gerenciamento de resíduos; Entulho; Waste